1998
DOI: 10.1089/thy.1998.8.505
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of C Cells in Hashimoto's Thyroiditis

Abstract: The objective of the present investigation was to study quantitatively C cells in Hashimoto's thyroiditis (HT) by analyzing 22 thyroids obtained at autopsy or thyroidectomy from 16 patients with thyroiditis and from 6 normal subjects. Six different areas were sampled on average and labeled with a monoclonal anticalcitonin antibody by immunohistochemistry using the avidin-biotin-peroxidase complex. Normal thyroids from adult patients with no thyroid disease were used as control. C cells were counted in 1 cm2 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
7
0
5
Order By: Relevance
“…Some authors have reported CCH in a number of thyroid specimens affected by Hashimoto's thyroiditis (Guyetant et al 1994). However, the association between thyroiditis and hypercalcitoninemia is still controversial (Karanikas et al 2004, Schuetz et al 2006 because some authors have reported decreased CT levels -in smaller groups of patients -that are probably caused by atrophy, fibrosis, and destruction of both follicular and C-cells (Body et al 1986, Borges et al 1998, Lima et al 1998, Poppe et al 1999. In addition to this, falsely high CT levels (or spurious hypercalcitoninemia) can be caused by the presence of heterophilic antibodies; this effect can be avoided through dilution techniques or sera pretreatment with blocking reagents (Giovanella & Suriano 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported CCH in a number of thyroid specimens affected by Hashimoto's thyroiditis (Guyetant et al 1994). However, the association between thyroiditis and hypercalcitoninemia is still controversial (Karanikas et al 2004, Schuetz et al 2006 because some authors have reported decreased CT levels -in smaller groups of patients -that are probably caused by atrophy, fibrosis, and destruction of both follicular and C-cells (Body et al 1986, Borges et al 1998, Lima et al 1998, Poppe et al 1999. In addition to this, falsely high CT levels (or spurious hypercalcitoninemia) can be caused by the presence of heterophilic antibodies; this effect can be avoided through dilution techniques or sera pretreatment with blocking reagents (Giovanella & Suriano 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The negative relationship between ECLIA-CT and TgAb in the present study suggested that CT level might be affected by HT. It has been reported that interference in measurement by antibodies or influence to C-cell by histological changes of thyroid gland induced by HT were possible mechanisms of the relationship [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Diğer bir çalışmada TSH düzeyi 5-10 mU/L olan 87 çocuk üç yıl boyunca izleminde % 41'inin TSH düzeyi <5 mU/L, % 20'sinin 5-10 mU/L ve % 39'unun TSH düzeyinin >10 mU/L olduğu bildirilmiştir (27 (19). HT patogenezindeki inflamatuar süreçte kalsitonin salgılayan C hücrelerinin de etkilenebileceği ve bunun sonucunda HT'li hastalarda hipokalsemi oluşabileceği bildirilmiştir (30).…”
Section: Tiroid Antikorlarının Varlığı (Anti-tpo Ve Antitg)unclassified